Kajian Pendahuluan: Perpindahan Gen dari Tanaman Kentang Transgenik Katahdin RB ke Tanaman Kentang Non Transgenik - Ambarwati, A. Dinar; Herman, M.; Purwito, Agus rifcb@indo.net.id; Sofiari, Eri; Aswidinnoor, hajrial (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTPreliminary study: Gene transfer from transgenic potato Katahdin RB to non transgenicpotato. One of the concerns associated with the release of transgenic crops, is the possibilityof the gene flow from transgenic crops to neighboring crops of the same species or to relatedspecies. In plants, gene flow is a routine process occur through the natural hybridization. Theopportunity for gene flow occur depends principally on two factors, the degree of sexualcompatibility between donor and recipient species, and the physical distance between thetwo. The experiment was conducted to determine whether the gene flow from transgenicpotato Katahdin RB to non transgenic was occurred, based on selection using a 50 mg/lkanamycin, and to estimate gene flow mediated by natural hybridization at different isolationdistances. Preliminary result indicated that a rapid and simple method using MS0 liquid mediawith kanamycin 50 mg/l was effective for screening the seeds. There was a gene flow fromtransgenic potato Katahdin RB to non transgenic, based on a rapid and simple selectionmethod using 50 mg/l of kanamycin as selectable marker. The isolation distance used in thestudy were 0.8, 1.6, 2.4, 3.2, 4.0, 4.8, 5.6, 6.4, 7.2, 8.0, 8.8, 9.6, 10.4, and 11.2 m from the row oftransgenic potato Katahdin RB. The gene flow through natural hybridization at a isolationdistances of (0.8 - 1.6 m), (2.4 â 4 m), and (4.8 â 6.4 m) from transgenic to non transgenic plantswere 13.78, 10.92, and 3.82%, respectively. At a distance of 7.2 â 8 m, the frequency of gene flowwas declined to 0%. The frequency of gene flow from transgenic potatoes to non transgenicpotatoes markedly decreased by increasing the isolation distance, and was negligible at 7.2 m.Key words : natural hybridization, transgenic potato RB, kanamycin selection